Предмет: Алгебра,
автор: kb5665788
729. 1) Докажите тождество: a) (a + b)a - (a - b)b = a² + b²; 6) (a + b)a - (a + b)b = a² - b²; B) (a + b)a + (a + b)b = a² + 2ab + b².
Ответы
Автор ответа:
29
Ответ:
Объяснение:
а) (a+b)a-(a-b)b=a²+ab-(ab-b²)=a²+ab-ab+b²=a²+ b²
б) (a + b)a - (a + b)b = a²+ab-(ab+b2)=a²+ab-ab-b²=a²- b²
в) (a + b)a + (a + b)b=a²+ab+ab+b²=a² + 2ab + b²
malika8575:
Надеюсь правильно ✅
Похожие вопросы
Предмет: История,
автор: lubaradis38
Предмет: Химия,
автор: sasausbel
Предмет: Алгебра,
автор: staskravtsov8
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним